Testing Phases for RFID Inventory Management System - Nazmi, Nurul Ainun Sollihah; Nik Ahmad, Nik Azlina (Journal of Computing Technologies and Creative Content, 2021)
The growth of a company means increases in productivity. With the increase of productivity comes an increase in products. For any growing business to succeed, it needs a good inventory management system. This study supports an RFID inventory management system and examines its usability assessment by evaluation of task performance and measurement of satisfaction using a system usability scale. This research includes the involvement of actual users with a total number of 20 staffs from Fateh Watches and 11 public users who had experience with management systems. The results showed that 90.32% of the users that tested the system were satisfied with the whole system functionality in overall. On the other hand, the other 9.78% participants are dissatisfied signifies that there is a need for improvement in the system.